Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) Terintegrasi Nilai-Nilai Aneka - Hardianto Hardianto; Lisa Aditya Dwiwansyah Musa (Journal of Teaching dan Learning Research, 2020)
Abstract[English]:The implementation of the Two Stay Two Stray (TSTS) type of cooperative learning process integrated with ANEKA values makes students learn not only receive knowledge, but also students learn to behaved well and speak good, so that it will create optimal learning conditions. This research was a descriptive research (descriptive research) which describes or explains systematically, factually, and accurately about the condition of the research subject being observed. The research subjects were the first semester students of Family Law Study Program class C for the 2019/2020 academic year, totaling 27 students, 13 male and 14 female. The data collection techniques used were observation, questionnaires, and documentation. The implementation of the cooperative learning model of the integrated TSTS type with ANEKA values has the following stages, (1) conveying goals and motivating students; (2) presenting information; (3) organize students into study groups; (4) help work, (5) evaluation; and (6) giving awards. Student activities during the learning process were in good categories and student responses to the application of the learning model were categorized as positive.Abstrak[Indonesia]:Penerapan proses pembelajaran kooperatif tipe Two Stay Two Stray (TSTS) yang terintegrasi dengan nilai-nilai ANEKA menjadikan siswa belajar tidak hanya menerima pengetahuan, tetapi juga siswa belajar berperilaku baik dan bertutur kata yang baik, sehingga tercipta kondisi belajar yang optimal. Penelitian ini merupakan penelitian deskriptif yang mendeskripsikan atau menjelaskan secara sistematis, faktual, dan akurat tentang kondisi subjek penelitian yang diamati. Subjek penelitian ini adalah mahasiswa Program Studi Hukum Keluarga kelas C tahun ajaran 2019/2020 yang berjumlah 27 mahasiswa, 13 laki-laki dan 14 perempuan. Teknik pengumpulan data yang digunakan adalah observasi, angket, dan dokumentasi. Penerapan model pembelajaran kooperatif tipe TSTS terintegrasi dengan nilai-nilai ANEKA memiliki tahapan sebagai berikut, (1) menyampaikan tujuan dan memotivasi siswa; (2) menyajikan informasi; (3) mengorganisir siswa ke dalam kelompok belajar; (4) membantu pekerjaan, (5) evaluasi; dan (6) pemberian penghargaan. Aktivitas siswa selama proses pembelajaran berada pada kategori baik dan respon siswa terhadap penerapan model pembelajaran dikategorikan positif.